2018
DOI: 10.1089/jwh.2017.6729
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal Loading Versus Sham Exercises to Improve Pain and Dysfunction in Postmenopausal Women with Greater Trochanteric Pain Syndrome: A Randomized Controlled Trial

Abstract: Lack of treatment effect was found with the addition of an exercise program to a comprehensive education on GTPS management. The improved outcomes of the responders in the GLoBE group indicate that there may be a subgroup of patients with a GTPS diagnosis that benefit from a GLoBE intervention program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 34 publications
4
68
1
6
Order By: Relevance
“…Recently, a progressive lower limb exercise programme for the gluteal, quadriceps and calf muscles was compared with sham exercise in postmenopausal females with GTPS. Both groups also received education and similar improvements were observed at 52 weeks 9. A randomised controlled trial of 204 participants with gluteal tendinopathy found that education plus a progressive exercise programme targeting the gluteal muscles was superior to both a corticosteroid injection and ‘wait and see’ approach at 8 and 52 weeks 10…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, a progressive lower limb exercise programme for the gluteal, quadriceps and calf muscles was compared with sham exercise in postmenopausal females with GTPS. Both groups also received education and similar improvements were observed at 52 weeks 9. A randomised controlled trial of 204 participants with gluteal tendinopathy found that education plus a progressive exercise programme targeting the gluteal muscles was superior to both a corticosteroid injection and ‘wait and see’ approach at 8 and 52 weeks 10…”
Section: Introductionmentioning
confidence: 83%
“…The ‘GLoBE’ trial compared gluteal loading with sham exercises in postmenopausal women with GTPS 9. Both groups received education on activity modification and avoiding tendon compression.…”
Section: Discussionmentioning
confidence: 99%
“…Gait retraining strategies to encourage GMax and GMin activation through the full range of a gait cycle, particularly into hip extension, may be considered. Further research into specific gluteal tendon loading program (Ganderton et al, 2018;Mellor et al, 2018) is warranted to inform clinicians on effectiveness and exercise parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for best-practice rehabilitation of this condition is limited and the most appropriate exercises are unknown (Ganderton et al, 2018;Mellor et al, 2018), despite the burden experienced by patients (Lievense et al, 2005;Segal et al, 2007;Rompe et al, 2009). Improved knowledge on the impact of the condition on gluteal muscle size and structure and may help to inform rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…On the opposite side, the evidence from the last three decades points to therapeutic exercise as the first-line treatment in tendinopathies due to its good short-term and long-term clinical outcomes and the non-existence of adverse effects 3–5 10. In this regard, different modalities of therapeutic exercise, such as isolated eccentric, combined eccentric and concentric, isometric or heavy slow resistance training, had shown positive outcomes on pain and function when controlled with placebo,11 surgery,12 passive treatment5 or other modalities of exercise groups 13 14…”
Section: Introductionmentioning
confidence: 99%